Efficacy and Safety of Neoadjuvant Targeted Therapy vs. Neoadjuvant Chemotherapy for Stage IIIA EGFR-Mutant Non-small Cell Lung Cancer: A Systematic Review and Meta-Analysis - Chen, Dong; Jin, Zixian; Zhang, Jian; Xu, Congcong; Zhu, Kanghao; Ruan, Yuhang; Zhang, Bo; Chen, Baofu; Shen, Jianfei (Frontiers in Surgery, 2021)
Purpose: The role of targeted therapy in the neoadjuvant field of stage IIIA EGFR-mut+ non-small cell lung cancer (NSCLC) is still controversial. We sought to evaluate the efficacy and safety of neoadjuvant targeted therapy (NTT) with neoadjuvant chemotherapy (NCT) used as a benchmark comparator. Methods: We systematically searched databases and included studies that compared NTT versus NCT for stage IIIA EGFR-mut+ NSCLC. The primary endpoints were overall survival (OS), progression-free survival (PFS), objective response rate (ORR), and grade 3/4 adverse events (AEs). RevMan was used to perform the meta-analysis. Results: A total of 319 patients were included in the analysis (264 in the subgroup analysis). The meta-analysis reveals that for EGFR-mut+ stage IIIA NSCLC patients, NTT has a trend to improve OS (hazards ratio [HR]:0.74, 95% confidence interval [CI]:0.43‒1.27; subgroup-HR:0.64 95%CI 0.40‒1.03), but there is no significant difference in PFS (HR:0.81, 95%CI 0.27‒2.44). NTT was associated with a significantly better ORR (relative risk [RR]:1.70, 95%CI 1.35‒2.15; subgroup-RR:1.56, 95%CI 1.23‒2.0). The incidence of grade 3/4 AEs in the NTT group was significantly reduced (RR:0.5, 95%CI 0.34‒0.75; subgroup-RR:0.53, 95%CI 0.26‒1.08). Conclusion: In neoadjuvant setting, targeted therapy has a definitive effect on patients with EGFR-mut+ stage IIIA NSCLC and is even better than chemotherapy in terms of toxicity and tumor response rate.